Food and feeding behaviour of the golden catfish, Horabagrus brachysoma (Gunther) - Padmakumar, K G; Bindu, L; Sreerekha, P S; Joseph, Nitta (Indian Journal of Fisheries, 2011)
Horabagrus brachysoma (Gunther, 1824), commonly known as golden catfish, is an endangered freshwater fish species endemic to the Western Ghats region of Peninsular India. The study was based on 246 fishes of total length ranging from 13 to 34 cm. Filamentous algae, detritus, fish offal, macro-vegetation, crustaceans and other miscellaneous items formed the food of H. brachysoma. Food intake was found to be reduced during pre-spawning and spawning months. The mean relative length of gut (RLG) recorded was 0.99.